Density Flies and Helminth Infection at Child in Muara Angke (Indian Journal of Public Health Research & Development, 2020)
Context: Infection due to worms can lead to anemia, nutritional disorders, growth, and intelligence whichin the long run will reduce the quality of human resources. This study aims to determine relevant of densityof flies to helminthiasis and to know relevant between risk variables (gender, age, latrine availability,cleanliness of nails, footwear habits, parental education, socio-economic conditions, floor conditions, foodsanitation). This study was an observational analytic study with a cross sectional approach with a totalsample of 97 people taken from the age of 7-15 years. Stool examination results showed that students whotested positive for helminthiasis were 5 people (5.2%) and negative as many as 92 people (94.8%). Based onstatistical analysis was concluded that there was irrelevant between fly density, sex, age, latrine availability,hygiene of nails, footwear habits, mother’s education, and food sanitation.
Keywords: Musca domestica; synanthropic ?ies; mechanical transmission; soil-transmitted helminth